Median nerve piercing the humeral head of pronator teres muscle: An anatomical case report of atypical median nerve formation and course - Y. Lakshmisha Rao; Archi Raj; Mangala M. Pai; Mamatha Tonse; Jasmeen Kaur; J.M. Likitha; B.V. Murlimanju (Translational Research in Anatomy)
Introduction: The objective of this study is to report the variant formation and course of the median nerve, which was observed in the right arm of a male cadaver. Methods: During the routine dissection procedure, it was observed that the median nerve was formed by the blending of three roots, which included one medial and two lateral roots. Results: It is also further observed that the median nerve pierced the humeral head of pronator teres just above the medial epicondyle and it passed through the cubital fossa more medially and deeper, making it invisible. Conclusion: Entrapment of median nerve by the pronator teres is among the causes of the proximal median nerve entrapment syndrome. In this context, this interesting and rare variation of pronator teres muscle being pierced by the median nerve will be of interest to the orthopedic specialists, neurosurgeons and hand surgeons. The present study also observed variant formation of the median nerve by triple roots, which is important both for the surgical and anesthesiologic perspective.